Dynamic Process and Mechanism of the Catastrophic Taihongcun Landslide Triggered by the 2008 Wenchuan Earthquake Based on Field Investigations and Discrete Element Method Simulations - Zhou, Xingtao; Wei, Pengfei; Fu, Xiaodong; Li, Lihua; Xue, Xiaohui (Frontiers in Earth Science, 2021)
The Taihongcun landslide, which was a remarkable geological disaster triggered by the 2008 Wenchuan earthquake, had a volume of about 2 × 106 m3 and killed about 23 people. Through detailed field investigations, basic information of topography, geological structure and stratigraphy for the landslide were acquired and key kinetic characteristics of the landslide were identified. On the basis of filed investigations, 2D numerical models with discrete element method (DEM) were established to simulate the kinematics and failure process of the landslide. To ensure the validity of the dynamic calculations, the free-field boundary condition was developed and introduced intro the DEM models. According to filed investigations and DEM simulations, the dynamic processes of the Taihongcun landslide can be divided into four phases: fragmentation, projection motion, scraping, and granular debris flow and accumulation. In addition, the parameter analysis showed that the particle bond strength had a significant influence on the runout distance and landslide debris morphology. Finally, the possible mechanism of the Taihongcun landslide was determined: a rock mass of poor quality provided the lithological basis for this landslide formation; a joint set J1 in the back scarp and a weak interlayer of carbonaceous slate and shale between the upper sliding mass and the bedrock formed the rupture boundaries of the upper source area; a strong seismic ground motion was the external excitation that triggered the destructive landslide event; additionally, hypermobility was caused by the high elevation and topographical conditions of the landslide.